Synthesis of Green Diesel from Palm Oil Using Nickel-based Catalyst: A Review - Aziz, Isalmi; Sugita, Purwantiningsih; Darmawan, Noviyan; Dwiatmoko, Adid Adep (Jurnal Kimia Valensi, 2023)
Petroleum is the primary energy that is generally used throughout the world. Its non-renewable nature and exhaust gas emissions that can damage the environment are a concern for developing environmentally friendly renewable energy. Green diesel is an alternative energy to replace diesel fuel (diesel) from petroleum which has the potential to be developed. The raw material in palm oil has great potential for development due to its relatively high production. Green diesel synthesis can be carried out using the catalytic deoxygenation method. The type of raw material, catalyst, and process conditions influences this method. The catalyst is the most influential factor in catalytic deoxygenation. Transition metal catalysts like nickel are inexpensive and have good catalytic activity like precious metals. Catalytic activity can be increased by modifying the catalyst components and optimizing the process. Modification of the catalyst can increase the surface area, Lewis and Bronsted sites, and crystal size so that the resulting green diesel can be maximized, such as Ni-Co, Ni-Zn, and Ni-Mo bimetallic catalysts.